The biology and pathobiology of von Willebrand factor - Lillicrap, David (Henry Stewart Talks, 2007)
Primary hemostasis, von Willebrand factor biochemistry and cell biology, von Willebrand disease diagnostic criteria, Molecular genetic pathology of type 3 vWD, Molecular genetic pathology of type 2A, 2B, 2M and 2N vWD, Mutational spectrum of type 1 vWD
Updated at 2021/01/19